Nanopartículas de poli(ácido láctico-co-glicólico) revestidas com quitosana contendo anfotericina B: desenvolvimento, caracterização e avaliação in vitro da eficácia e toxicidade - Ludwig, Daniel Brustolin (2019)
Systemic fungal infections consist of the leading causes of mortality among hospitalized immunocompromised patients. Amphotericin B (AmB) is the drug of choice in these situations because it is a broad spectrum antifungal. Despite its effectiveness, AmB is used only through parenteral route, as it has low oral bioavailability, as well as renal cell toxicity. It also has activity on the immune system and ability to form reactive oxygen species (ROS), which assists in antifungal activity but also in the toxicity of the molecule. In this study, chitosan-coated (poly-lactic-co-glycolic) acid (PLGA) nanoparticles containing AmB were developed and evaluated for oral application. The choice of polymers was due to the biocompatibility and the mucoadhesive characteristics of chitosan. The nanoparticles were developed by the emulsion-solvent evaporation method and had a mean diameter of 204 ± 22 nm, a polydispersion index of 0.197 ± 0.01 and an encapsulation efficiency of 93.3 ± 0.4 %. The zeta potential of +21 ± 0.8 mV was compatible with the presence of chitosan on the surface. The results of X-ray diffraction studies and thermal analysis demonstrated amorphization of AmB after nanoencapsulation and consequently an improvement in stability of the molecule. The in vitro release profile was prolonged and biphasic, releasing 56 % of AmB after 120h. The nanoparticles were stable in simulated gastric and intestinal media, promoting an AmB release of 0.2 % and 1.4 %, respectively. In the results of the in vitro determination of the mucoadhesive capacity it was observed that the chitosan promoted the interaction of the nanoparticles with mucin. The nanoparticles reduced significantly the AmB cytotoxicity on erythrocytes and Vero cells demonstrating compatibility with the results obtained in the aggregation assay, where AmB released from the system prevails in the monomeric state, that is, more soluble and less toxic form. The in vitro assay of antifungal efficacy on strains of Candida spp. and Trichosporon spp. showed the action of the nanoparticles containing AmB in reducing the amount of fungal colony forming units (CFU) by determining the minimum inhibitory concentration (MIC) compared to the free AmB. Thus, AmB chitosan-coated PLGA nanoparticles are promising alternative for the treatment of systemic fungal infections by the oral route.